Unveiling the Silence: The Crucial Role of Muslim Intellectuals in Promoting Peace within Islam - Mohammad Salih Mustafa (CV. FOUNDAE, 2026)
In an era of escalating anti-Islamic sentiments, the absence of vocal engagement from Muslim intellectuals unintentionally facilitates recruitment efforts of extremists targeting Muslim youth. Extremist groups exploit a narrative positioning themselves as the sole defenders of Islam, distorting its essence and fuelling further radicalisation. Despite the potential for religions to foster peace, the silence of Muslim intellectuals creates a void exploited by extremist groups, hindering peace efforts within Islam. This study explores the reasons behind this silence and emphasises the critical role of Muslim intellectuals in promoting peace within their religion. Through an extrapolation analysis of existing data and literature, this study identifies challenges and perceptions of tolerance in Islam, the role of religion and religious figures in peace-making, and strategies for countering misconceptions about the rejection of violence by Islam. The findings reveal a lack of confidence among Muslim intellectuals, intensified by pervasive Islamophobia and dilemmas in advocating for peace amidst political polarisation. Therefore, urgent action is needed to empower Muslim intellectuals in supporting the message of peace and countering extremist narratives within Islam, thereby contributing to global peace efforts.